The truth is in the isotopes: Authenticating regionally unique South African lamb. (15th January 2018) - Erasmus, Sara W.; Muller, Magdalena; Butler, Mike; Hoffman, Louwrens C.
Highlights: Stable isotope ratios were determined for South African lambs. Differences in the isotope ratios of lambs from different regions were found. Isotope ratios were indicative of the extensive grazing diet of the lambs. The δ 13 C and δ 15 N values increase moving towards the Northern parts of the country. Abstract: Stable isotope ratios ( 13 C/ 12 C and 15 N/ 14 N) of South African lambs from different regions were measured by isotope ratio mass spectrometry (IRMS). Homogenised and defatted meat of the Longissimus lumborum muscle was assessed. The Rûens and Hantam Karoo regions had the lowest (P ≤ 0.05) δ 13 C values related to the presence of C3 plants (lucerne and Karoo bushes, respectively). The Northern Karoo, Namibia and Bushmanland had the highest δ 13 C values likely due to a high proportion of dietary C4 grass species. The δ 15 N values were highest for Central Karoo, Semi-extensive, Namibia and Hantam Karoo, while Rûens and Feedlot had the lowest nitrogen isotope values (P ≤ 0.05). Classification of origin (Karoo vs. Non-Karoo) using discriminant analysis allowed 95% and 90% correct classification of the samples for the estimation model and validation models, respectively. The results confirm that IRMS provides sufficient discriminative power to classify lamb meat of varying origin.